Development and implementation of bottom ash crushing system in Submerged Scrapper Conveyor (SSC) for Coal-fired Power Plant - Basim Ismail F.; Why Siew Kuan E.; Shakir Nasif M. (EDP Sciences, 2023)
Ash handling; Ashes; Coal; Coal fueled furnaces; Computer software; Conveying; Conveyors; Crushing; Mining; Safety factor; Slags; Soot; Boiler furnaces; Chain breakage; Coal-fired power plant; Conveying systems; Current performance; Scrapper conveyor; Stress strain; Sudden loading; Fossil fuel power plants